Geochemical characteristics and origin of crude oil from Carboniferous volcanic rocks in the Hongche Fault Zone of the Junggar Basin of China - He, Qingbo; Chen, Shijia; Wang, Jian; Zhao, Liping; Ma, Zhiwei (Frontiers in Earth Science, 2022)
In recent years, significant advances have been made in the exploration of Carboniferous volcanic reservoirs in the Hongche Fault Zone of the Junggar Basin of China, showing good prospects for further exploration. However, the large variation in the physical properties of crude oil and the complex distribution rule inhibit the one-step exploration. In this study, the PM scale of the biodegradation of crude oil and source of crude oil were studied using experimental methods that target the properties, bulk properties and biomarker compounds of crude oil. The exploration potential of crude oil in this area was analysed, and an accumulation model of crude oil was established. Based on the differences in biomarker compounds and the degree of biodegradation, crude oils were divided into four groups and seven subgroups. Additionally, the analysis of the biomarker compounds of crude oil combined with the hydrocarbon-generation history of source rocks showed that there were at least two periods of oil charging in this area. The first period was the late Triassic, with crude oil derived from the P1f source rock. Owing to the strong tectonic activity during the late Indosinian movement, the oil reservoirs were distributed in the footwall of the fault zone, and the oil in the reservoir exhibited different degrees of biodegradation, forming crude oils of subgroup I1, II and III1. The second period was Cretaceous, during which the P1f source rock was in the natural gas generation stage, and the P2w source rock was at a mature stage. A small part of the crude oil formed by the P2w source rock migrated to the Carboniferous reservoirs and mixed with the crude oil formed by the earlier P1f source rock, resulting in crude oils of subgroups I2, III2, and IV2. The crude oil in the studied area originated from the source rocks in the sag during the peak of oil generation. As tectonic activity approached stability in the latter period, it is speculated that there may be well-preserved primary oil and gas reservoirs in the footwall and slope areas of the fault, making these potential exploration sites.